Noninvasive Maternal–Fetal Hemodynamic Monitoring as A Predictor of Severe Preeclampsia in Low-Resource Settings: A Case Report - Toledo-Jaldin, Lilian; Gomez, Richard; Lazo-Vega, Litzi; Larrea, Alison; Vásquez, Adolfo; Ormachea-Orellana, Wilson; Miranda-Garrido, Valquiria; Julian, Colleen G. (American Journal of Perinatology Reports, 2025)
Preeclampsia is a multiorgan vascular disease complicating approximately 8.5 million pregnancies worldwide annually and is a leading cause of maternal and neonatal mortality. The impact is especially severe in Latin America, where maternal deaths attributable to preeclampsia are 2.5 times higher than in any other region. Bolivia is particularly affected due to economic and environmental challenges, including high altitude, which increases the risk of fetal growth restriction and hypertensive disorders of pregnancy. Early and accessible diagnostic tools are required to maximize patient care and improve reproductive outcomes in limited-resource settings. This report details a case from Bolivia of rapid-onset severe preeclampsia with liver rupture in the third trimester; the patient required multiple surgical interventions for recurrent liver bleeding and extended hospitalization in the intensive care unit (ICU). She delivered a preterm, growth-restricted infant with signs of acute hypoxia by emergency cesarean section. Notably, 2 weeks before ICU admission, abnormal uterine artery and maternal hemodynamic measurements were detected, without other signs of preeclampsia. The patient had previously been healthy and was considered low risk. Both mother and newborn survived. This case underscores the value of combining uterine artery Doppler with maternal hemodynamics to identify high-risk pregnancies early and prevent life-threatening complications.
Keywords: preeclampsia; early detection; hemodynamics; low-resource settings